Body weight misperception patterns and their association with health‐related factors among adolescents in South Korea. (31st May 2013) - Lim, Hyunjung; Wang, Youfa
<x xml:space="preserve">Abstract</x> Objective Examined body weight misperception and its association with health‐related factors among South Korean adolescents. Design and Methods The 2009 Korea Youth Risk Behavior Web‐based Survey data from 72, 399 adolescents aged 12‐18 years were used. Based on agreements between weight status assessed according to self‐reported BMI and self‐perceived weight status, adolescents were classified as weight underestimate, accurate, and overestimate. Logistic regression models examined the associations controlling for covariates. Results Over 50% adolescents misclassified their own weight status: underestimation (23.4%) and overestimation (26.8%). Boys had a higher underestimation rate than girls (30.3% vs. 15.6%) and a lower overestimation rate (21.3% vs. 33.0%). In girls, overestimation was higher in high‐income families and well‐educated parents (41.0%). Compared to those with accurate weight perception, participants who underestimated their weight were more likely to have an unhealthy diet as indicated by higher daily consumption (≥once/day) of fast food [OR = 1.18 (1.00, 1.39)] and unhealthy snacks [OR = 1.11 (1.03, 1.19)]. Girls who overestimated their weight had more screen time [≥2 h/day, OR = 1.12 (1.03, 1.22)]. Participants who overestimated their weight were more likely to be stressed [OR = 1.24 (1.18, 1.31)] and depressed [OR = 1.18 (1.21, 1.25)]. Conclusions Over half of Korean adolescents had misperception on own weight status, the rates varied by gender and socioeconomic status. Weight misperception is associated with health‐related outcomes compared to peers with accurate perceptions about own weight status.